Exposing Medical Education’s Hidden Curriculum through an Exploration of Teacher-Learner Relationships - Jodi Jarecke; Edward W. Taylor (Adult Education Research Conference, 2010)
The purpose of this study was to explore third-year medical students’ perceptions of their teacher-learner relationships with their clinical educators.